GREEN BUSINESS: CHALLENGES AND PRACTICES - Čekanavičius, Linas; Bazytė, Rugilė; Dičmonaitė, Agnė (Ekonomika, 2014)
Abstract. The paper deals with the relatively new worldwide trend of adding a “green” slant to business. The purpose of the research was twofold: firstly, to clarify the definition of “green business”, secondly, to test the hypothesis that the differences in business penetration by “green” ideas in various countries are to a large extent determined by national specifics in terms of economic development and public consciousness. Authors compare and contrast the commonly found definitions of “green business”, clarify a distinction between the “green business” notion and that of “sustainable business”, define the main agents of the business “greening” trend, discuss what it means to be “green” and what business practices qualify it as “green”. A quantitative empirical research method – a survey via a questionnaire distributed to respondents by e-mail or handed in directly – was used for the second purpose of the study. The survey was conducted by the authors in Lithuania and Ireland. The collected primary data were processed with the SPSS program and analysed by methods of correlation analysis. The research has revealed considerable differences in the “green” attitudes and practices of Lithuanian and Irish companies, the former being more concerned with costs than benefits of becoming “green”, and the latter demonstrating awareness that being “green” opens new revenue-raising opportunities.Key words: green business, environmental awareness, green attitudes and practices